A mathematical model to mimic the shape of event related desynchronization/synchronization. (14th September 2018) - Baghdadi, Golnaz; Towhidkhah, Farzad; Rostami, Reza
Highlights: The proposed mathematical model can produce the pattern of ERD and ERS. The proposed model has been designed based on the forced synchronization concepts. Simulation results show the effect of some factors on ERD and ERS latency and amplitude. In the proposed model, an oscillatory activity with specific frequency increases after the onset of a stimulus. Some suggestions about reasons behind the effect of some parameters have been provided. Abstract: Rhythmic oscillatory activities of the sensory cortex have been observed after a presentation of a stimulus. This activity first drops dramatically and then increases considerably that are respectively named event-related desynchronization (ERD) and event-related synchronization (ERS). There are several effective factors that can alter the ERD and ERS pattern. In this study, a mathematical model was presented that produced ERD and ERS pattern in response to a stimulus. This model works based on the synchronization concepts. The proposed model provided different suggestions about the reason behind the relationship between the encoding of incoming sensory information and the oscillatory activities, effective factors on the characteristics of neuronal units, and how may these factors affect the amplitude and latency of the ERD and ERS.